Effects of Vibration Characteristics on the Atomization Performance in the Medical Piezoelectric Atomization Device Induced by Intra-Hole Fluctuation - Qiufeng Yan (SpringerOpen, 2021)
Abstract Oral inhalation of aerosolized drugs has be widely applied in healing the affected body organs including lesions of the throat and lungs and it is more efficient than those conventional therapies, such as intravenous drip, intramuscular injection and external topical administration in the aspects of the dosage reduction and side effects of drugs. Nevertheless, the traditional atomization devices always exhibit many drawbacks. For example, non-uniformed atomization particle distribution, the instability of transient atomization quantity and difficulties in precise energy control would seriously restrict an extensive use of atomization inhalation therapy. In this study, the principle of intra-hole fluctuation phenomenon occurred in the hole is fully explained, and the produced volume change is also estimated. Additionally, the mathematical expression of the atomization rate of the atomizing device is well established. The mechanism of the micro-pump is further clarified, and the influence of the vibration characteristics of the atomizing film on the atomization behavior is analyzed theoretically. The curves of sweep frequency against the velocity and amplitude of the piezoelectric vibrator are obtained by the Doppler laser vibrometer, and the corresponding mode shapes of the resonance point are achieved. The influence of vibration characteristics on atomization rate, atomization height and atomization particle size are also verified by experiments, respectively. Both the experimental results and theoretical calculation are expected to provide a guidance for the design of this kind of atomization device in the future.